Characterization of Electronic Cigarette Warning Statements Portrayed in YouTube Videos. Issue 8 (5th January 2021) - Jones, Dina M; Guy, Mignonne C; Soule, Eric; Sakuma, Kari-Lyn K; Pokhrel, Pallav; Orloff, Mohammed; Trinidad, Dennis; Smith, Denelle; Browley, Sharaka; Walker, A Paige; Bullock, Sandilyn; Eissenberg, Thomas; et al.
Abstract: Introduction: In 2018, the United States Food and Drug Administration (FDA) required that electronic cigarette (e-cigarette) manufacturers, packagers, importers, distributors, and retailers display an addictive or alternate warning statement on e-cigarette visual advertisements. Few studies have investigated the FDA-mandated and other warnings on social media. This study examined the prevalence and content of warning statements in e-cigarette-related YouTube videos. Methods: In 2019, The Virginia Commonwealth University Center for the Study of Tobacco Products conducted bi-monthly (February-June) YouTube searches by relevance and view count to identify e-cigarette-related videos. Overall, 178 videos met the inclusion criteria. Staff coded each video for the presence of a visual/verbal warning statement, warning statement type (eg, FDA-mandated, addiction/tobacco, safety/toxic exposure, health effects), sponsorship, and tobacco product characteristics. A data extraction tool collected the video URL, title, upload date, and number of views, likes/dislikes, and comments. Results: Only 5.1% of videos contained FDA-mandated and 21.9% contained non-mandated warnings. All videos with FDA-mandated and 46.2% of non-mandated warnings were represented visually. Only 13.1% of industry-sponsored videos uploaded after the mandate effective date had an FDA-mandated warning statement and videos with FDA-mandated and non-mandated (v. no) warnings had significantly fewer views, likes, dislikes, and comments. Among all non-mandated warnings, 31.3% featured an addiction/tobacco, 18.8% a safety/toxic exposure, and 37.5% a health effects warning. Conclusions: The prevalence of FDA-mandated warning statements in e-cigarette related YouTube videos was low. FDA enforcement of the warning statement mandate on YouTube could increase the public's understanding of the addictive nature of nicotine in e-cigarettes. Implications: The FDA has the authority to regulate the advertisement and promotion of e-cigarettes on the Internet. These data can inform future FDA requirements related to the language content and visual representation of addiction/tobacco, safety/exposure, and health effects warning statements that appear in YouTube videos and other visual social media popular among young people. Such data would help consumers make informed decisions about purchasing e-cigarette products, using e-cigarettes, and avoiding unintentional harm related to e-cigarettes. In addition, these data may help social media platforms make decisions on whether they will prohibit advertisements that promote or facilitate the sale of tobacco products.